A comunicação na comunidade discursiva da Igreja Católica Apostólica Romana: das Cartas dos Apóstolos a gêneros textuais atuais - Martins, Sandra Eleutério Campos (2014)
The purposes of this study are to carry out a survey, characterization and description of the genders used currently in the correspondence between the Holy See, the other members and the faithful of the Apostolic Roman Catholic Church, as well as in Saint Paul s Epistles, bringing out evidence that the first have their origin in the texts written by the apostles, mainly Saint Paul. The theoretical basis for the study is found in the studies concerning the concept of genre characterization and of discursive community, more precisely Bakhtin (2003) and Travaglia (2007, 2009). Concerning the correspondence genre, we adopted Kaufman and Rodriguez (1995) and Bazerman (2006). We also analyzed the writings of Fremantle (1956), Polhill (1999), Trobisch (2001) and Silva (2008), whose works refer to Saint Paul s Epistles. We started the research, making a description of the configuration of Saint Paul s Epistles. Simultaneously, we carried out a survey, with the Catholic religious community, of the genres of text written by the Pope, or on his behalf, of which we selected ten. We proceeded, then, to the description and characterization of all these texts, establishing the relationship between them and the Saint Paul s Epistles. The results show that the socio-communicative functions carried out by Saint Paul s Epistles in the communities of the primitive church, are alive currently in the religious discursive community of Apostolic Roman Catholicism, by various genres of texts sent by the Pope to Catholics in the whole world, who, constitute, thus, an actualization of the texts produced by Saint Paul, at the time in which he lived and carried out his role of Church Leader. Complementarily, we characterized and distinguished ten genres of the discursive community of Apostolic Roman Catholics produced by the Pope which the evidence indicates would be derived from the apostles, mainly Saint Paul.